#Barbie and Social Media
XXIII, 238 p. 7 illus., 3 illus. in color.
Keywords: Hains and Aguiló-Pérez have assembled a superb collection of essays that examine how Barbie enters and informs the cultural imagination through social media. Recognizing that the Barbie doll signifies for adults as much as it does for young people, this highly accessible volume will appeal to academics and non-academics of all ages. - Claire Katz, Ph.D., co-editor of In a Barbie World: Barbie as Narrative, Symbol, and Cipher. #Barbie and Social Media offers a fresh yet timeless exploration of the famous doll as a brand, activist icon, site of critique, and so much more. With implications for areas as diverse as marketing, gender and identity studies, and online activism, this volume is essential reading for anyone thinking about culture and social media today. - Brooke Foucault Welles, Ph.D., co-author of #HashtagActivism: Networks of Race and Gender Justice #Barbie and Social Media delves into Barbie’s transformation from doll to global cultural icon–one that is deeply embedded in contemporary social media discourse. It explores how digital platforms have given rise to a dynamic, participatory culture that both celebrates and critiques doll and brand. From Mattel’s strategic branding of Barbie as a symbol of diversity and empowerment, to individuals' use of social media to reimagine Barbie’s identity and significance, #Barbie and Social Media offers a comprehensive examination of Barbie in the digital age. Rebecca C. Hains is a professor of Media & Communication at Salem State University, USA. She is an author and co-editor of numerous books and articles on children’s media culture, including Growing Up With Girl Power: Girlhood on Screen and in Everyday Life (2012); The Princess Problem (2014); Cultural Studies of LEGO: More than Just Bricks (2019); and Supernatural Youth in Media (2025). Emily R. Aguiló-Pérez is a professor of English (Youth Literatures & Cultures) at West Chester University of Pennsylvania, USA. She has authored and co-edited numerous books and articles, including An American Icon in Puerto Rico: Barbie, Girlhood, and Colonialism at Play (2022); Islas Lectoras: Bibliografía infantil puertorriqueña (2023); and The Cultural Legacy of Disney: A Century of Magic (2024). .